Non-Acute Myeloid Neoplasms With CD34(-) Blasts: Immunophenotypic And Clinical Analysis Of 5 Cases. (28th October 2020) - Shponka, V; Kroft, S; Harrington, A M; Monahan, K; Atallah, E
Abstract: Introduction/Objective: Non-acute myeloid neoplasms (NAMNs) comprise clonal hematopoietic disorders, characterized by ≤20% myeloblasts in the peripheral blood (PB) and/or bone marrow (BM). The blasts of NAMN are almost exclusively CD34(+), contrasting with blasts in some acute myeloid leukemias (AML). We detail the clinicopathologic features of NAMN with CD34(-) blasts. Methods: We searched 981 NAMN pathology reports for CD34(-) blasts by flow cytometry (FC). 8-color FC data was analyzed using cluster analysis to identify all relevant cell populations with a comprehensive antibody panel. CD34(-) blast populations were defined as reproducible clusters with similar light scatter properties across antibody tubes, after exclusion of other cell populations (e.g. basophils, neutrophils, mast cells). Blast aberrancies were defined as differences from established normal antigen expression patterns. PB and BM morphology was reviewed and chart reviews were performed. Results: We identified 5 NAMN patients with CD34(-) blasts (2M, 3F; 57-84y/o) including 3 myelodysplastic syndrome (MDSs) with excess blasts, 1 therapy-related MDS, and 1 chronic myelomonocytic leukemia-1 (CMML). Blasts ranged from 0-1.5% in PB and 2.8-8% in BM. CD34(-) blasts accounted for 0.85-8.2% of BM events by FC, with all showing other aberrancies. The CMML patient had CD34(-) blasts with monocytic differentiation; all other CD34(-) blast populations showed expression of CD13, CD33, and CD117 and aberrant under-expression of CD38. Aberrancies were also present in the CD34(+) blasts in all patients (1-4/patient), accounting for 0.01-0.55% of events; 3/5 pts had under-expression of CD33, CD38, CD45, and/or HLA-DR. No cases had adverse cytogenetics. Patient outcomes included: indolent disease (1); died from disease 3 years post-diagnosis and chemotherapy (1); transformed to AML (2; 1-alive in complete remission; 1-died); and alive following allogeneic stem cell transplant (1). Conclusion: Our data confirm that CD34(-) blasts are rarely observed in NAMN, and these patients have variable outcomes. Interestingly, all cases showed a concomitant aberrant CD34(+) blast population.